Propose framework for developing an e-Home service as web advertisement in e-Commerce / Zuliana Mohamed - Mohamed, Zuliana (2006)
There is an issue in marketing on how to attract the customer in a competitive Internet marketplace. This research analyzes the features requirement of existing e-home service website and identify how e-marketers can influence the outcome of the virtual interaction and buying process. This framework of e-home service website is actually one of the guideline to make an expand stage. From the analyze of features in e-home service website and evaluation of stage of development of framework, the framework is then developed to make Internet user easier to access from anywhere. In fact, the framework of e-home service will be proposed. At the same time, a set of questionnaire is using as checklist in order to assemble the data. Thereafter, the originality or value of this research will recommend and put forward the features that are important for developing an e-home service Website. The illustration of framework is propose and user interface design involves the development of prototype interfaces to be suitable for evaluating the different between others website.